2006
DOI: 10.3349/ymj.2006.47.6.782
|View full text |Cite
|
Sign up to set email alerts
|

Urachal Anomalies in Children: A Single Center Experience

Abstract: The objective of this study is to define optimal diagnosis and treatment strategies for patients with urachal anomalies in the pediatric age group. The medical records of 21 children who had undergone surgery for urachal anomalies at Severance Hospital, Yonsei University College of Medicine from January 1990 to April 2005 were reviewed. The subjects included 14 males and 7 females (M:F 2:1). The four types of urachal anomalies confirmed were a urachal cyst in 10 patients (47.6%), a patent urachus in 6 (28.6%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 18 publications
1
66
0
4
Order By: Relevance
“…Although rare, urachal anomalies are more prevalent in males than in females [Cilento et al, 1998;Nascimento et al, 2004;Choi et al, 2006;McCrystal et al, 2007]. In this study, we observed some structural differences in the fetal urachus between sexes at the same gestational age.…”
Section: Discussionsupporting
confidence: 66%
“…Although rare, urachal anomalies are more prevalent in males than in females [Cilento et al, 1998;Nascimento et al, 2004;Choi et al, 2006;McCrystal et al, 2007]. In this study, we observed some structural differences in the fetal urachus between sexes at the same gestational age.…”
Section: Discussionsupporting
confidence: 66%
“…Our truly positive ultrasound diagnoses (64%) are substantially below their percentage, which may be caused by a relatively small patient collective of 10 patients reviewed by Yapo and coworkers [27]. The diagnostic accuracy of US in urachal remnants has been described in several studies to vary from 61.1% to 100% [8,21,28].…”
Section: Discussionmentioning
confidence: 89%
“…The argument used to justify surgical excision at the time of diagnosis was that urachal anomalies rarely resolve without such radical intervention and that they care a risk of recurrence and of malignant transformation [11]. Similar justification has been used in other studies for surgical excision of urachal anomalies, particularly those that are symptomatic [12,14].…”
Section: Surgery Versus Observationmentioning
confidence: 94%
“…A number of studies have suggested antibiotics followed by incision and drainage prior to definitive surgical excision is the optimal approach to infected urachal cysts [13,48]. This approach has been shown to reduce the rate of postoperative wound infection to zero [14]. In one of the few studies to include both approaches, of 26 patients who underwent surgical excision for symptomatic urachal anomalies, 25 % of those who underwent a primary one-stage repair developed infectious postoperative complications, whereas no postoperative complications were recorded in those who underwent a staged approach with preoperative antibiotics [26].…”
Section: Surgical Managementmentioning
confidence: 99%